ANALISIS ASUHAN KEPERAWATAN DENGAN INTERVENSI INOVASI TERAPI GUIDED IMAGERY PADA KLIEN DIABETES MELITUS YANG MENGALAMI KECEMASAN DI TELAGA MURNI BEKASI - Nabilah Tiani Rachman (2022)
Diabetes is a chronic disease that occurs either when the pancreas does not produce enough insulin or when the body cannot effectively use the insulin it produces. Diabetes mellitus has a negative impact on the patient's physical and psychological. Negative impacts that arise on the psychological such as anger, feeling useless, depression and anxiety. Anxiety is a subjective feeling of restless mental tension as a general reaction of the inability to cope with a problem or lack of security. Guided imagery is a technique that uses an individual's imagination with a directed imagination to reduce anxiety. This analysis aims to determine the results of guided imagery therapy on anxiety in Diabetes Mellitus patients. This analysis uses 2 samples of respondents, 1 respondent managed and 1 respondent resume. At the beginning of the study, both patients had the score from the Hamilton Rating Scale For Anxiety (HARS) questionnaire, which was 23 for managed patients and 24 for resume patients who were included in the moderate anxiety category. The results showed that both patients who were given the intervention had a score decreased to less than 14, which means that their anxiety decreased and could be categorized as non-existent.